Conference on Scientific and Social Research (CSSR) 2004 - Wee, Cindy (UiTM Sarawak, 2004)
A three-day conference (CSSR 2004) on the theme "World Class University Through Research Excellence" drew a large crowd of over 350 researchers throughout the UiTM campuses to share their research findings. The event which was held at the Crowne Plaza Hotel in Kuching on 19 to 21 May 2004 saw as many as 158 research papers from a wide range of disciplines being presented.